Operations Improvement Function and Economic Sustainability of Petroleum Tank Farms in South South, Nigeria - Dr. Needorn. R. S.; Dr. Okoisama. T. C.; Agbiriogu. E. K. (Research Parks Publishers, 2022)
The study examines the link between operations improvement function (dimensioned by contingency planning and preventive maintenance) and economic sustainability of petroleum tank farms in South-South, Nigeria. The study was underpinned by the stakeholder theory and the theory of routine dynamics. The study adopted the cross-sectional survey research design, as the researchers could not manipulate the variables, and the underlying philosophy is positivism. The questionnaire was the instrument for data collection. The elements of the accessible population comprise 820 middle and top level managers of all the 29 petroleum tank farms owned by members of the Independent Petroleum Products Importers, in South South, Nigeria. The Krejcie & Morgan’s formula was deployed to determine the sample size of 262 respondents, and a 10% provision was reasonably made to accommodate non-responses and outliers, bringing the adjusted sample size to 288 respondents. The simple random sampling technique was adopted and the Structural Equation Modeling was deployed to test the hypotheses at 0.05 significance level.The results revealed that contingency planning and preventive maintenance have positive and significant relationships with economic sustainability.